Back Massage terhadap Nyeri dan Luaran Persalinan: Literature Review: Literature Review of Back massage Therapy on Labor Pain dan Outcomes - Ekadewi Retnosari (Indonesian Journal of Midwifery (IJM), 2024)
One of the most common problems during labor is pain during contractions. There are many non-pharmacological interventions that are carried out, one of which is back massage. There has been a lot of research on back massage, therefore the researcher aims to find out literature reviews about the effect of back massage on pain and other outcomes of childbirth. The literature review method using the PRISMA approach was used in this literature review. Data synthesis uses the PICO method. Article sources used were Google Scholar, Pubmed NCBI and Scopus. The inclusion criteria set were articles with the keyword Back massage”. "Labor", "Childbirth", "pain", "back massage", "pain" and "labor", articles in Indonesian or English, published in 2012-2022, and can be accessed in full text. Results: There were 8 articles used in the literature review. The results obtained were 17 articles synthesized in this study. All research shows that back massage has an effect on reducing labor pain. Labor pain measurements are carried out using different tools, most of which use a visual analog scale. Apart from labor pain, it also shows that back massage can reduce cortisol, shorten the duration of labor, reduce anxiety and increase maternal satisfaction with labor, however there is no difference in the APGAR Score. Midwives using back massage can help reduce the mother's perception of pain during labor. Abstrak Salah satu masalah terbanyak pada persalinan dalah nyeri pada saat kontraksi. Banyak intervensi non famakologi yang dilakukan salah satunya dengan back massage. Telah banyak penelitian tentang back massage oleh sebab itu peneliti bertujuan untuk melakukan literatur review tentang pengaruh back massage terhadap nyeri dan luaran lain persalinan. Metode tinjauan pustaka dengan pendekatan PRISMA digunakan dalam tinjauan pustaka ini. Sintesis data menggunakan metode PICO. Sumber artikel yang digunakan melalui Google Scholar, Pubmed NCBI dan scopus. Kriteria inklusi yang ditetapkan adalah artikel dengan kata kunci Back massage” . ”Labor“, “Childbirth”, “pain”, “back massage”, “nyeri” dan “ persalinan”, artikel dalam bahasa Indonesia atau Inggris, diterbitkan pada tahun 2014-2024, dan dapat diakses dalam teks lengkap. Hasil: Terdapat 45 artikel sesuai kata kunci, kemudian sebanyak 17 artikel disentesis pada penelitian ini. Seluruh penelitian menunjukkan bahwa back massage berpengaruh terhadap penurunan nyeri persalinan. Pengukuran nyeri persalinan dilakukan dengan alat yang berbeda dengan sebagian besar menggunakan visual analog scale. Selain nyeri persalinan juga menunjukkan bahwa  back massage dapat menurunkan kortisol, memperpendek durasi persalinan, menurunkan kecemasan dan meningkatkan kepuasan ibu terhadap persalinan, namun demikian tidak ada perbedaan pada APGAR Score. Back massage dapat dilakukan bidan sebagai upaya mengurangi persepsi nyeri persalinan.